Managing Depression among Diverse Older Adults in Primary Care: The BRIGHTEN Program. Issue 2 (15th March 2017) - Emery-Tiburcio, Erin E.; Mack, Laurin; Lattie, Emily G.; Lusarreta, Montserrat; Marquine, Maria; Vail, Matthew; Golden, Robyn
ABSTRACT: Objectives : A variety of specific cultural adaptations have been proposed for older adult and minority mental health interventions. The objective of this study was to determine whether the BRIGHTEN Program, an individually tailored, interdisciplinary "virtual" team intervention, would equally meet the needs of a highly diverse sample of older adults with depression. Methods : Older adults who screened positive for depression were recruited from primary and specialty care settings to participate in the BRIGHTEN program. A secondary data analysis of 131 older adults (37.4% African-American, 29.0% Hispanic, 29.8% Non-Hispanic White) was conducted to explore the effects of demographic variables (race/ethnicity, income and education) on treatment outcome. Results : Compared to baseline, participants demonstrated significant improvements on the SF-12 Mental Health Composite and depression (GDS-15) scores at 6-month follow-up. There were no differences on outcome measures based on race/ethnicity, income or education with one exception—a difference between 12th grade and graduate degree education on SF-12 Mental Health Composite scores. Conclusions : While not explicitly tailored for specific ethnic groups, the BRIGHTEN program may be equally effective in reducing depression symptoms and improving mental health functioning in a highly socioeconomically and ethnically diverse, community-dwelling older adult population. Clinical Implications : Implications for behavioral health integration in primary care are discussed.